KARYA TARI “SOLAH” REFLEKSI NILAI-NILAI BUDAYA JAWA DALAM KEHIDUPAN KEKINIAN - Dwiyasmono Dwiyasmono (Universitas Gadjah Mada, 2015)
Solah, is a dance work of Dwiyasmono as a director, describes every people do to get what they want inevery ways. This work started from knowledge about passions in Islam (mutmainah, amarah, sufiah andaluamah) and Javanese’s wisdom about keblat papat lima pancer. Solah as an explorative dance work,its movements based on traditional dance such as Surakarta dance style, folk style, ritual, mythologyand oral tradition. Solah is a reflection for people and situation nowadays to understand about rightor wrong and true or false for everything we did, as an ethical based to test people’s psychology aboutthinking and doing.